Analysis of Participatory Accounting System Transformation in Strengthening Risk Management and Regulatory Compliance in Village-Owned Enterprises (BUMDes) - Meikhati, Ety; Sundari; Oktaviani, Intan (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study investigates the transformation of participatory accounting systems and their role in strengthening risk management and regulatory compliance within Village-Owned Enterprises (BUMDes). Many BUMDes still face limitations in financial governance capacity, weak internal controls, and inconsistent fulfillment of regulatory requirements. Participatory accounting, characterized by transparency, collaborative decision-making, and stakeholder engagement, is introduced as a strategic mechanism for improving financial accountability. Using a mixed-methods approach, this research integrates qualitative interviews, field observations, and document analysis with quantitative measurement of risk management and compliance indicators before and after the accounting transformation. The findings reveal that the participatory accounting transformation significantly enhances the accuracy and reliability of financial reporting, reinforces internal control mechanisms, and improves the identification, assessment, and mitigation of operational and financial risks. In addition, the transformed system increases regulatory compliance, particularly in standardized financial reporting, procedural adherence, and audit preparedness. This study concludes that participatory accounting constitutes a critical driver of resilient financial governance and promotes long-term accountability and sustainability of BUMDes. The results provide practical implications for policymakers, village governments, and BUMDes managers in designing adaptive accounting systems that foster transparency, stakeholder participation, and compliance with national regulations.